Original paperA novel predictor of infarct-related artery patency before percutaneous intervention and in-hospital outcomes for ST-segment elevation myocardial infarction patients: serum bilirubin level - Acet, Halit; Ertas, Faruk; Akıl, Mehmet Ata; Polat, Nihat; Aydın, Mesut; Akyüz, Abdurrahman; Ayçiçek, Hilal; Alan, Sait (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Previous studies have reported a relationship between serum bilirubin levels and coronary artery disease (CAD). However, data are rare up to now regarding the relation of bilirubin levels with infarct-related artery (IRA) patency in the setting of ST-segment elevation myocardial infarction (STEMI). Moreover, previous studies reported that increased bilirubin was related to impaired post-intervention coronary flow. To our knowledge, the association between serum total bilirubin (TB) levels and pre-primary percutaneous coronary intervention (PCI) with patency of IRA flow in STEMI patients has not been investigated. Aim: To evaluate the association of TB with pre-primary PCI, coronary flow and in-hospital major adverse cardiac events (MACE) in patients with STEMI. Material and methods : A total of 360 consecutive patients with STEMI (mean age = 61.4 ±13.7 years) admitted within 12 h from the time of symptom onset were enrolled. Patients were divided into 2 groups based on the serum TB levels. We defined normal flow as pre-PCI TIMI 3 flow, while impaired flow was defined as pre-PCI TIMI ≤ 2 flow. Results : Pre-PCI impaired flow was higher in the TB group than pre-PCI normal flow (p < 0.001). In-hospital mortality and MACE were significantly higher in the high TB group (p = 0.002, p 0.825 mg/dl predicted impaired IRA flow before p-PCI with a sensitivity of 79% and specificity of 71%. Conclusions : The TB is an inexpensive and readily available marker for STEMI patients undergoing PCI. It can be used for risk stratification in this patient population.